Variation in plasma cholinesterase activity in the clay-colored robin (Turdus grayi) in relation to time of day, season, and diazinon exposure - Cobos, Víctor M; Mora, Miguel A; Escalona, Griselda; Calme, Sophie; Jiménez, Juan (Ecotoxicology (London), 2010)
Cholinesterase (ChE) activity in birds is subject to interspecific and intraspecific species variations. Factors that influence enzyme activity have to be taken into account in order to obtain an accurate estimation of cholinesterase inhibition due to pesticide exposure in wild birds. This study evaluates variation of plasma cholinesterase activity in clay-colored robin (Turdus grayi) in relation to time of day, season, and exposure to diazinon. Other variables that can affect cholinesterase activity such as weight are also taken into account. The birds were marked, weighed and sexed using the cloacal technique. One dose of commercial diazinon mixed with papaya was fed to each bird at concentrations of 0.0, 0.5, 1.5 and 3.0 mg/kg ai. The results showed differences in ChE activity between seasons (t = −3.07, P < 0.05). Also, diurnal plasma cholinesterase variations were observed (20% in 2 h). The highest inhibition values were 73% for birds dosed with 1.5 mg/kg ai. Our study provides field and laboratory data on variation of ChE activity in a tropical bird species. Knowledge of the variation of ChE in the clay-colored robin will enable us to use this species as an indicator of exposure to ChE inhibiting pesticides in tropical agroecosystems.